2021
DOI: 10.1111/bjh.17394
|View full text |Cite
|
Sign up to set email alerts
|

Insight into del17p low‐frequency subclones in chronic lymphocytic leukaemia (CLL): data from the Australasian Leukaemia and Lymphoma Group (ALLG)/CLL Australian Research Consortium (CLLARC) CLL5 trial

Abstract: The clinical significance of low-frequency deletions of 17p13 [tumour protein p53 (TP53)] in patients with chronic lymphocytic leukaemia (CLL) is currently unclear. Low-frequency del17p clones (<25%) were identified in 15/95 patients in the Australasian Leukaemia and Lymphoma Group (ALLG)/CLL Australian Research Consortium (CLLARC) CLL5 trial. Patients with low del17p, without tumour protein p53 (TP53) mutation, had significantly longer progression-free survival and overall survival durations than patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In this series 0.7% of p53 deficient cases were missed by NGS of which 8 cases had a del(17p) clone size of less than 25%. Also recent data showing low-frequency del(17p) sub clones (<25% of CLL cells) in the absence of a TP53 mutation has been demonstrated to mirror that of cases with no del(17p) in the chemoimmunotherapy setting ( 12 , 19 ). In the study by Do et al 15/20 (75%) patients demonstrated a low frequency subclone of del(17p) (<25)).…”
Section: Discussionmentioning
confidence: 92%
“…In this series 0.7% of p53 deficient cases were missed by NGS of which 8 cases had a del(17p) clone size of less than 25%. Also recent data showing low-frequency del(17p) sub clones (<25% of CLL cells) in the absence of a TP53 mutation has been demonstrated to mirror that of cases with no del(17p) in the chemoimmunotherapy setting ( 12 , 19 ). In the study by Do et al 15/20 (75%) patients demonstrated a low frequency subclone of del(17p) (<25)).…”
Section: Discussionmentioning
confidence: 92%